How to learn to discriminate signs of manipulation (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
Today it seems difficult to discriminate between public and private, to discriminate signs of manipulation that invade the limits of the inner person and compel to actions. The starting point is to identify the learning history of the person and if he or she was respected by his ideas, intuitions and theories different from the group. To speak of manipulation is to talk about aversive control. The criterion to accept verbalizations is analyzed in the context of life. The motivation, reinforcement to adopt or try a new repertoire, in therapy, it is decided in each moment. It means to guarantee, through the external control constructed by the person, the way to obtain the internal objectives connected with natural reinforcement. In the case of manipulation the control is based upon arbitrary reinforcement. We need, in therapy, to teach observation that is the way the client has to know, his own needs and not the controller’s.